China and the global economy : national champions, industrial policy, and the big business revolution - Nolan, Peter, 1949- (Houndmills : Palgrave, 2001)
This text tells the story of China's emergence as a major economic power and the impact this will have on world business. It is an executive summary of the opportunities for business in one of the largest markets in the world.
Includes bibliographical references : pages 233-234 and index.
Keywords: International economic relations; China -- Economic conditions -- 1976-2000.; China -- Economic policy -- 1976-2000.